การพัฒนาชุดกิจกรรมการเรียนรู้วิทยาศาสตร์ โดยใช้วัฏจักรการเรียนรู้ 7 ขั้น ร่วมกับผังมโนทัศน์ และการเรียนรู้แบบสร้างสรรค์เป็นฐาน ที่มีผลต่อการคิดวิเคราะห์ ความคิดสร้างสรรค์ และผลสัมฤทธิ์ทางการเรียน ของนักเรียนชั้นมัธยมศึกษาปีที่ 3 - Maikham, Metavadee; Klangprapan , Marasri; Palajit, Somkiat (Journal of Graduate School Sakon Nakhon Rajabhat University, 2022)
The purposes of this research were: 1) to develop science learning activity packages using the 7Es learning cycle, concept mapping, and creativity-based learning for Mathayomsuksa 3 students to achieve the defined effectiveness index, 2) to compare students’ analytical thinking, creativity, and learning achievement before and after the intervention, and 3) to compare the analytical thinking, creativity and learning achievement of students with diverse scientific minds after the intervention. The sample, obtained through cluster random sampling, was a class of 42 Mathayomsuksa 3 students at Mukdahan school under the Secondary Educational Service Area Office 22 in the second semester of the 2019 academic year. The research instruments were: 1) the science learning activity packages, 2) an analytical thinking test, 3) a creativity test, 4) a learning achievement test, and 5) a scientific mind test. The statistics for data analysis were mean, standard deviation, effectiveness index, t-test for Dependent Samples, One-Way ANOVA, and One-Way MANOVA. The findings were as follows: 1. The developed science learning activity packages based on the 7Es learning cycle, concept mapping, and creativity-based learning achieved the effectiveness index of 0.58, which was higher than the defined criteria of greater than .05. 2. The students’ analytical thinking, creativity, and learning achievement after the intervention were higher than those before the intervention at the .05 level of significance. 3. The analytical thinking, creativity, and learning achievement of students with diverse scientific minds after the intervention was different at the .05 level of significance.